Analyzing the Public Perception of Brawl Phenomena Involving Juvenile Delinquency in Jakarta - Aulya Syifa Sagita (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
This paper aims to explain the use of reception theory in the case of public perception of brawl phenomena in Jakarta. The phenomenon that has been going on for years amongst Junior High School students and Senior High School students is a problem that has never ended. This issue is of significant concern due to the fact that teenagers in Indonesia, particularly within the Jakarta region, do not appear to be dissuaded by government sanctions. Consequently, a substantial number of these juvenile delinquents continue to engage in altercations between schools. Therefore, this paper focuses its attention on the reactions of individuals to reports of criminal activities involving juvenile delinquency and people’s perspectives on the Indonesian legal framework applied to this demographic. The approach employed in this paper is a qualitative methodology centered on phenomenological research, complemented by reception theory. This combined approach aids the researcher in elucidating the phenomena that occur among delinquents and in examining how the media covers these incidents.